Listewki skorne streiy podpalcowej st6p u ludnosci Polski pdlnocnej - Buchwald, Wiesław (Polskie Towarzystwo Antropologiczne, 1988)
DERMATOGLYPHIC TRAITS OF THE SUB-TOE AREA OF SOLES IN THE POPULATION OF NORTHERN POLAND. The frequencies of occurrence of patterns in five fields of the sub-toe area of soles in 1,600 men and 1,600 women from 15 voivodships of northern Poland were demonstrated. The bilateral and intersexual differences were examined and the obtained results compared with the pattern frequencies in the population from central and south-eastern Poland.
DERMATOGLYPHIC TRAITS OF THE SUB-TOE AREA OF SOLES IN THE POPULATION OF NORTHERN POLAND